Ramblin' on my mind : new perspectives on the blues - Evans, David, 1944- (African American music in global perspective., 2008)
Distinguished scholars and well-established writers from such diverse backgrounds as musicology, anthropology, musicianship, and folklore join together to examine blues as literature, music, personal expression, and cultural product.